Endemic Vesical Stones in Sudanese Children Seen at Gezira National Center for Pediatric Surgery - Osman, Mohanned A M; Nugud, Faisal A; Osman, Osman T M (مجلة الجزيرة للعلوم الصحية; مجلد 10 عدد 1 (2014), 2014)
Objectives: To determine the pattern, demographic features, clinical features, the common types of vesical stones and diagnostic tools accuracy of endemic vesical stone in children. Materials and Methods: In this study the records of 73 patients with endemic vesical stones were reviewed at Gezira National Center For Pediatric Surgery (GNCPS). The data were analyzed for age, sex, locality, clinical features the diagnostic tools, the treatment offered and outcomes. Results:   A total of 73 patients were included in this study, males were 64  (87.7%), < 5 years were  54 cases ( 74%), the majority from rural areas of low socio-economic status.   Conclusion: Endemic vesical stones in children is common in males below  5 years  and low socio-economic status, with UTI like symptoms and penile itching.